Acoustical Imaging Volume 30 - André, Michael P.; Jones, Joie P.; Lee, Hua (Acoustical Imaging, 2011)
The International Symposium on Acoustical Imaging is a unique forum for advanced research, covering new technologies, developments, methods and theories in all areas of acoustics. This interdisciplinary Symposium has been taking place every two years since 1968. In the course of the years the proceedings volumes in the Acoustical Imaging Series have become a reference for cutting-edge research in the field. In 2009 the 30th International Symposium on Acoustical Imaging was held in Monterey, CA, USA, March 1-4. Offering both a broad perspective on the state-of-the-art as well as  in-depth research contributions by the specialists in the field, this Volume 30 in the Series contains an excellent collection of forty three papers presented in five major categories: Biomedical Imaging Acoustic Microscopy Non-Destructive Evaluation Systems Analysis Signal Analysis and Image Processing Audience Researchers in medical imaging and biomedical instrumentation experts.